PENGARUH TEKNIK ROLE PLAYING UNTUK MENGURANGI KECEMASAN BERBICARA DI DEPAN KELAS MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 21 PEKANBARU - Elisa, Elisa; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This research aims to know the differences of class speaking anxiety before and after the given role playing techniques through group guidance to reduce the anxiety of speaking in front of the class. This research was done in the SMP Negeri 21 Pekanbaru on 7 subjects with a purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. Data collection instruments used is the now the anxiety of speaking in front of the class is adapted from Nofrans (2009). The results showed that there is a difference in the thinking and after the given role playing techiniques with a value of significance 0,018 < 0,05. The influence of the techniques of acting against the anxiety of speaking infront of the class through the guidance of the group is 61,7% while 38,3% affected by other factors that originate from within and from the learners.Key Words : Role Playing, Speaking of Anxiety, The Guidance Group